PUBLIC PROCUREMENT AS A TOOL TO STIMULATE INNOVATION IN UZBEKISTAN ON THE EXAMPLE OF THE EXPERIENCE OF CHINA (International Journal of Innovative Technologies in Economy, 2021)
The state of public procurement as a tool for stimulating innovation is analyzed both in developed countries and in Uzbekistan. It is proposed to conclude that at different stages of placing and executing a government order, there are many risks, especially in countries where there is still a centralized procurement organization. It is necessary to use special methods of placing a state order and establish high qualification requirements both for the customer's personnel and for the specialists involved.